Evaluation of Erosion Potential and Determination of The Causes of Erosion Using A Geographic Information System - Lestari, Alisa; Simanjuntak, Bistok Hasiholan (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2022)
The purpose of this study was to determine the magnitude of the erosion class and too determine the cause distribution area in the Upper Serang Sub-watershed. In this study using combinatian of quantitative and qualitative descriptive methods. While the tools used are GPS, soil sampling tools, laboratory test equipment such as permeability analysis tools, organic materials tools, texture analysis tools, data analysis tools using Arc Gis 10.4.1 and SPSS. Erosion potential analysis using USLE (Universal Soil Loss Equation) method. Based on the research results, the Upper Serang Sub-watershed has 5 erosion class categories, i,e very light class (0.5-10.11 tÂ·haâ€“1Â·yâ€“1). Light grade (15.26-48.52 tÂ·haâ€“1Â·yâ€“1). Medium class (70.55-164.51 tÂ·haâ€“1Â·yâ€“1). Heavy class (208.95â€“388.41 tÂ·haâ€“1Â·yâ€“1). Very heavy class (697.47â€“2241.14 tÂ·haâ€“1Â·yâ€“1). While the Erosion Hazard Index is divided into 4 classes, i,e low class with a value of <1. Medium class with a score of 1.001-4.00. High class with a value of 4.01â€“10.0. Very high grade with a score of > 10. The dominant factor influencing the high and low erosion value is the slope factor and the length of the slope at the location of the Upper Serang Sub-watershed based on the closeness value with a value of 0.935 with a very strong closeness class. Â Keywords: Erosion, USLE, Serang Upper, Sub-watershed